Integrated approach to solve pollution and biodiversity conflicts in Malaysia - Ismail, Ahmad (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2014)
Pollution and human activities affect biodiversity and it can be either direct or indirectly. A direct one usually occur through oil spill, acute chemical pollution, deforestation, overharvesting, etc. while indirect one often contaminate the environment affecting single or a group of organism within the food chains. Continuous chemical accumulation of hazardous chemicals not only disrupt target organism but also cause impairments or abnormalities in subsequent generations. For examples, there were many studies that highlighted the effects of heavy metals to waterbirds population including their young such as thinning of eggshells, deformities, low survival, etc. Many other cases relating to us humans are also well publicised as our health and life quality deteriorates in conjunction with hazardous chemical pollution, overexploitation and habitat degradation. The important question remains, how to solve pollution problems? Integrated approach that considers fundamental sciences, land availability and its uses, social awareness and education background is very much needed to help solving this issue. Through public recognition and support, implementing a green policy would be easier. This process can be hastened by providing accurate and up to date evidence for the public to act upon. Hence, the ultimate goal of any good scientist is not only to obtain important information from our surroundings, but also to deliver the right message and help promote awareness, develop commitment and to seek balance between public’s needs and ecosystem’s stability.